2015
DOI: 10.1074/jbc.m114.614420
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Synaptic GTPase-activating Protein (synGAP) by Ca2+/Calmodulin-dependent Protein Kinase II (CaMKII) and Cyclin-dependent Kinase 5 (CDK5) Alters the Ratio of Its GAP Activity toward Ras and Rap GTPases

Abstract: Background: synGAP inactivates Ras and Rap at synapses. Results: Phosphorylation of synGAP by CaMKII increases Rap1 GAP activity more than HRas GAP activity; phosphorylation by CDK5 has the opposite effect. Conclusion: Phosphorylation by CaMKII and CDK5 alters the ratio of Rap1 and HRas GAP activities. Significance: Phosphorylation of synGAP by CaMKII and CDK5 can alter the balance of synaptic functions regulated by Ras and Rap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 59 publications
7
89
1
Order By: Relevance
“…This means that simple loss of syn-GAP from the spine would be expected to cause a greater increase in active Rap in the spine and a loss of surface AMPARs, in contrast to the model proposed by Araki et al. Indeed, we found that phosphorylation of synGAP by CaMKII doubles the rate of synGAP’s inactivation of Rap [36]. Thus, one of the same phosphorylation events that promotes detachment of synGAP from the PSD, also causes its rate of inactivation of Rap to increase, not decrease.…”
Section: The Role Of Syngap In Induction Of Ltpcontrasting
confidence: 82%
See 2 more Smart Citations
“…This means that simple loss of syn-GAP from the spine would be expected to cause a greater increase in active Rap in the spine and a loss of surface AMPARs, in contrast to the model proposed by Araki et al. Indeed, we found that phosphorylation of synGAP by CaMKII doubles the rate of synGAP’s inactivation of Rap [36]. Thus, one of the same phosphorylation events that promotes detachment of synGAP from the PSD, also causes its rate of inactivation of Rap to increase, not decrease.…”
Section: The Role Of Syngap In Induction Of Ltpcontrasting
confidence: 82%
“…Expression of active Rap in neurons accelerates endocytosis of AMPARs; whereas, expression of active Ras has the opposite effect, accelerating exocytosis of AMPARs [35]. The fold stimulation of Rap inactivation by synGAP is considerably higher than its stimulation of inactivation of Ras [36*]. This means that simple loss of syn-GAP from the spine would be expected to cause a greater increase in active Rap in the spine and a loss of surface AMPARs, in contrast to the model proposed by Araki et al.…”
Section: The Role Of Syngap In Induction Of Ltpmentioning
confidence: 99%
See 1 more Smart Citation
“…CaMKII links Ca 2+ elevations to downstream cellular targets responsible for LTP and sLTP by phosphorylating diverse substrates (Barria et al, 1997; Murakoshi et al, 2011; Opazo et al, 2010; Walkup et al, 2015; Yang et al, 2013). At its basal state, CaMKII is locked in an inactive state through the binding of a regulatory segment to its substrate binding site.…”
Section: Introductionmentioning
confidence: 99%
“…Over-expression of different isoforms resulting from various combinations of amino and carboxyl termini has different effects on synaptic strength judged by the amplitude and frequency of mEPSCs (McMahon et al 2012). Moreover, not only CaMKII but also Cdk5 whose translocation to the PSD is mediated by CaMKII regulates the activity of SynGAP toward Ras and Rap differentially (Walkup et al 2015). Thus, CaMKIImediated regulation of SynGAP activity is more complex than initially thought and needs further investigation.…”
Section: Syngapmentioning
confidence: 98%